Evaluation of physico-chemical and organoleptic characteristics of sweetened stirred plum (Prunes domestica) yoghurt during storage - Arora, Shalini; Chaudhary, Gaurav; Yadav, Upasana; Singh, Tarun Pal; Bathla, Shikha (Indian Journal of Dairy Science, 2021)
The objective of the present study was to develop sweetened stirred fruit yoghurt incorporated with plum fruit pulp. The pulp was added @ 10, 15 and 20% and the formulated sweetened fruit yoghurt was studied for various physico-chemical (pH, acidity, syneresis, and tyrosine value) and organoleptic characteristics during storage. Plain (natural) and plum yoghurt were observed significantly different and the results showed a significant (p